Matemática Aplicada à Topografia - Zucchi Neto, Antonio Donato (2017)
This work presents the relation between basic knowledge of geometry and trigonometry with topography, with emphasis on tachometry. The work consists of a brief history and some topography concepts, of the theoretical mathematical foundation necessary for the demonstrations of formulas used in topographical calculations, examples of applying trigonometry and geometry in obtaining inaccessible distances and the procedures to perform the calculations of a survey planimetric by polygon. It is presented a suggestion of classes involving topography in order to better develop mathematical contents in a practical way and with that to asome the interest of the students.